Gestational diabetes and the risk of late stillbirth: a case–control study from England, UK. (19th March 2019) - Stacey, T; Tennant, PWG; McCowan, LME; Mitchell, EA; Budd, J; Li, M; Thompson, JMD; Martin, B; Roberts, D; Heazell, AEP
Abstract : Objective: To explore the separate effects of being 'at risk' of gestational diabetes mellitus (GDM) and screening for GDM, and of raised fasting plasma glucose (FPG) and clinical diagnosis of GDM, on the risk of late stillbirth. Design: Prospective case–control study. Setting: Forty‐one maternity units in the UK. Population: Women who had a stillbirth ≥28 weeks of gestation ( n = 291) and women with an ongoing pregnancy at the time of interview ( n = 733). Methods: Causal mediation analysis explored the joint effects of (i) 'at risk' of GDM and screening for GDM and (ii) raised FPG (≥5.6 mmol/l) and clinical diagnosis of GDM on the risks of late stillbirth. Adjusted odds ratios (aOR) were estimated by logistic regression adjusted for confounders identified by directed acyclic graphs. Main outcome measures: Screening for GDM and FPG levels Results: Women 'at risk' of GDM, but not screened, experienced 44% greater risk of late stillbirth than those not 'at risk' (aOR 1.44, 95% CI 1.01–2.06). Women 'at risk' of GDM who were screened experienced no such increase (aOR 0.98, 95% CI 0.70–1.36). Women with raised FPG not diagnosed with GDM experienced four‐fold greater risk of late stillbirth than women with normal FPG (aOR 4.22, 95% CI 1.04–17.02). Women with raised FPG who were diagnosed with GDM experienced no such increase (aOR 1.10, 95% CI 0.31–3.91). Conclusions: Optimal screening and diagnosis of GDM mitigate the higher risks of late stillbirth in women 'at risk' of GDM and/or with raised FPG. Failure to diagnose GDM leaves women with raised FPG exposed to avoidable risk of late stillbirth. Tweetable abstract: Risk of #stillbirth in gestational diabetes is mitigated by effective screening and diagnosis. Tweetable abstract: Risk of #stillbirth in gestational diabetes is mitigated by effective screening and diagnosis.